Jalan Kesempurnaan Menurut Jamaah Insan Al-Kamil di Cijati Desa Cikareo Selatan Sumedang - Syarifudin Syarifudin (UIN Sunan Gunung Djati Bandung, 2020)
Each religious sect has its own characteristics, whether fundamental, radical, or religious. One of them is Insan Al-Kamil Congregation, which is in Cijati, South Cikareo Village, Wado District, Sumedang Regency. This congregation is Sufism with the concept of self-purification as the subject of its teachings. So, the purpose of this study is to reveal how the origin of Insan Al-Kamil Congregation, the concept of its purification, and the procedures of achieving its purification. This research uses a descriptive qualitative method with a normative theological approach as the blade of analysis. In addition, the data generated is the result of observation, interviews, and document studies. From the collected data, Jamaah Insan Al-Kamil adheres to the core teachings of Islam and is the tenth regeneration of Islam Teachings, which refers to the Prophet Muhammad SAW. According to this congregation, self-perfection becomes an obligation that must be achieved by human beings in order to remember Allah when life is done. The process of self-purification is done when human beings still live in the world by knowing His God. Therefore, the peak of self-purification is called Insan Kamil.Â